A new system and legal regulation of administrative punishment in the Czech Republic - Potěšil, Lukáš (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
This paper focuses on the new legal regulation that came into effect on 1.07.2017. This represents a relatively new approach to punishment realized by the administrative bodies. The new legal regulation has changed the system of administrative delicts itself as well as practice of administrative bodies. Not only in Poland, where there was a newly-adopted new legal regulation in the Administrative Code KPA, but also in the Czech Republic, we can see how the phenomenon of administrative punishment is becoming important and is an important part of the functioning of public administration. This paper would like to analyze important changes as well as some questions that the new legal regulation in the Czech Republic has brought.
Keywords: przestępstwo administracyjne; kara administracyjna; organy administracyjne